From Coin-Jars to QR Codes: How UPI is rewriting the household budgets of Chennai’s Middle-Class Women - Dr. R. Sundari, Dr. Srividya Prathiba C.S (European Economic Letters (EEL), 2025)
Background: In Indian homes, women have long perfected the art of micro-saving—coins tucked inside dabbas of turmeric, notes slipped behind spice jars, rotating kitty circles. These tiny, invisible reservoirs have often rescued families from sudden expenses and seeded larger dreams. Yet, a quiet technological tide—Unified Payments Interface (UPI)—is washing over these rituals. This study peers into the kitchens, handbags and smartphones of middle-class women in Chengalpattu, Kanchipuram and Chennai to ask: Has the tap-and-pay era diluted their legendary thrift, or is it simply giving that thrift a new, faster engine? Objective: This paper is an attempt to measure the impact of UPI on the probable changes in the spending and saving pattern among the middle-class women residing in Chengalpattu, Kanchipuram and Chennai district. Methodology: A Structured Questionnaire is used to measure the level of awareness, adoption and their level of spending and saving using UPI. Exploratory Factor Analysis is applied to explore study variables. A structural Equation Model depicting the interrelationship among the study variables are presented. Findings: Higher UPI awareness and adoption among women users materially alter their saving or investment behaviour. Conclusion: The study concludes that the transfer of surplus from a woman’s UPI balance into an interest-bearing instrument to a very great extent. The enduring appeal of the masala dabba lies in its silent discretion: though digital balance can be exposed with a single shared password, unlike the spice box that keeps its contents—and its owner’s financial intentions—known only to her still, economic empowerment has seen an immense growth.